2017
DOI: 10.12659/ajcr.903580
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Gastrointestinal Carcinoid Tumor and Colon Adenocarcinoma: Case Reports and Literature Review

Abstract: Case seriesPatient: Male, 40; Male, 70Final Diagnosis: Synchronous gastrointestinal carcinoid tumor and colon adenocarcinomaSymptoms: WeaknessMedication: —Clinical Procedure: ColonoscopySpecialty: Gastroenterology and HepatologyObjective:Rare co-existance of disease or pathologyBackground:Coexistence of carcinoid tumor and colorectal adenocarcinoma is rare. In this report, we present two cases and review the current literature for synchronous carcinoid tumor and colorectal carcinoma occurrence.Case Reports:In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
(8 reference statements)
0
20
0
Order By: Relevance
“…Gastrointestinal pan-adenocarcinomas accounted for an estimated 183,780 new cases and an estimated 77,280 deaths in the United States in 2018 [ 17 ]. Clinically, most individuals are diagnosed at an advanced stage, when effective curative therapies are not satisfactory, which renders advanced gastrointestinal pan-adenocarcinomas one of the most lethal cancers globally [ [18] , [19] , [20] , [21] ]. Therefore, it is imperative to more deeply explore molecular mechanisms in the prognosis of gastrointestinal pan-adenocarcinomas patients.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal pan-adenocarcinomas accounted for an estimated 183,780 new cases and an estimated 77,280 deaths in the United States in 2018 [ 17 ]. Clinically, most individuals are diagnosed at an advanced stage, when effective curative therapies are not satisfactory, which renders advanced gastrointestinal pan-adenocarcinomas one of the most lethal cancers globally [ [18] , [19] , [20] , [21] ]. Therefore, it is imperative to more deeply explore molecular mechanisms in the prognosis of gastrointestinal pan-adenocarcinomas patients.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the literature in English reveals, 20 case reports (18 synchronous cases [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], 2 metachronous cases [25,26]), 2 case series [25,27], 3 review articles [28][29][30], and about 10 retrospective studies [31][32][33][34] or population-based studies from a National Registry [35][36][37][38][39][40][41] of synchronous or metachronous NET with a second primary malignancy (SPM). A total of 31 patients in 24 articles were included in the study: 28 patients with a synchronous gastrointestinal NET and colorectal adenocarcinoma (Table 1) and 3 patients (including the present study) of 3 articles with metachronous gastrointestinal NET and colorectal adenocarcinoma ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Pearson and Fitzgerald were the first to report the high incidence (23%) of second primary malignancies (SPM) in patients with small intestinal NETs at autopsy [27]. A certain number of NETs were incidentally found during surgery for other [7] 1972 53 M Rectum Rectum -Lotlikar et al [25] 1981 53 M Rectum Small bowel -Lotlikar et al [25] 1981 67 F Right colon Small bowel -Lotlikar et al [25] 1981 60 F Sigmoid colon Small bowel -Sacchi et al [8] 1988 57 M Right colon Small bowel -Tse et al [9] 1997 72 M Hepatic flexure Small bowel -Habal et al [28] 2000 52 M Sigmoid colon Rectum Cioffi et al [10] 2005 64 F Ileum Small bowel -Klucinski et al [11] 2006 72 F Transverse colon Small bowel -Chemli et al [12] 2007 63 F Right colon Small bowel -Aslam et al [13] 2009 67 F Sigmoid colon Small bowel G1 Boland et al [14] 2009 77 F Left colon Meckel's diverticulum -McHugh et al [15] 2009 74 F Rectum Small bowel -Wohadlo et al [29] 2011 53 M Splenic-hepatic flexure Small bowel -Gurzu et al [16] 2012 78 F Sigmoid colon Small bowel G3 Pozzato et al [17] 2012 61 M Right colon Duodenum G1 Katalinic 2014 et al [18] 2014 63 M Right colon Meckel's diverticulum G1 Zhu et al [19] 2015 64 F Rectum Rectum G1 Almajano et al [20] 2016 66 M Right colon Small bowel G1 Mohapatra et al [21] 2016 83 M Sigmoid colon Left colon G3 Nejatollahi et al [22] 2016 83 M Sigmoid colon Small bowel G1 Vootla et al [23] 2016 46 F Hepatic flexure Rectum G1 Winn et al [30] 2017 40 M Sigmoid colon Rectum G1 Winn et al [30] 2017 70 M Sigmoid colon Rectum G1 Napolitano et al [24] 2017 72 M Right colon Small bowel G1-G2 cancers. The estimated rate of SPM associated with other malignancies was 2.3% in surgical cases and 8.1% in autopsy cases [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in some of the English literature that NETs are associated with synchronous or metachronous secondary primary malignancies (SPMs): rates of SPMs are up to 55% in NETs [25], and Tichansky et al reported that 8% of patients with colorectal carcinoid also had synchronous cancer [26]. Additionally, Winn et al reported that in synchronous colon adenocarcinomas with a gastrointestinal carcinoid tumor, the most common location was the sigmoid colon [2]. There are several hypotheses to explain the relationship between NETs and SPMs, including the field-effect theory, the stem cell theory, the neuropeptides theory, the genetic defect hypothesis, and the immunodeficiency theory [25,[27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs) are relatively rare, but are frequently associated with synchronous or metachronous secondary primary malignancies [1]. Although a few cases of synchronous colorectal cancer with gastrointestinal neuroendocrine tumors (GI-NETs) have been reported [2][3][4], to the best of our knowledge there are no cases in which a surgical resection was performed for cancer and chemotherapy for a GI-NET with multiple organ metastases. Here, we report a rare case where the patient was diagnosed with synchronous colorectal cancer and a rectal NET and underwent colectomy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%